Scientific - practical recommendations on improvement of regional nature in the Republic of Kazakhstan. (Journal of Economic Research & Business Administration, 2015)
The proposed Article Method of regional rankings in terms of impact on the environment is an important tool to identify "pain" points of these regions. The rankings used to determine the attractiveness of the territories in the implementation of long-term economic development strategies (eg, for purposes of recreational nature, the production of environmentally friendly products).